Knowledge and attitudes toward recreational cannabis legalization among California residents: a population-matched questionnaire about Proposition 64 - Daniel Ageze; Sara Baird; Thomas D. Marcotte; Ahmed Elashmawy; Angela Wong; Renee Dell’Acqua; Jill Rybar; Sarah Hacker; Alice Gold; Tom Shaughnessy; Ilene Lanin-Kettering; Linda L. Hill (Journal of Cannabis Research)
Abstract Background Implemented in 2018, Proposition 64: The Adult Use of Marijuana Act (Prop 64; passed in 2016) legalized adult recreational cannabis use in California. This analysis of the Impact 64 study aimed to assess knowledge about Prop 64 and attitudes toward cannabis legalization by California residents. Methods A mixed qualitative and quantitative questionnaire about cannabis and Prop 64 was completed by 4,020 current cannabis users, 523 former users, and 635 non-users who were selected from an initial pool demographically matched to the 2020 California census. Quantitative questions about Prop 64 knowledge and attitudes were selected for this sub-analysis. Chi-squared tests and nominal logistic multivariate analysis were used to assess knowledge and attitudes based on demographic characteristics and cannabis use factors. Results Current users had a mean age of 42 years and were 59% male, and more than 90% had heard of Prop 64. The 71% of current users who described themselves as somewhat or very familiar with Prop 64 were more likely to be employed full-time (AOR 1.5, p < 0.001), have no minors in the household (AOR 1.4, p < 0.001), and live in Central California (AOR 1.3, p < 0.001). Awareness of specific regulations of the associated laws was low among current users, including for possession (49%), transportation (41%), and gifting (30%) of cannabis, as well as for age and possession limits. Attitudes were mixed, though current users had more positive attitudes than former and non-users for almost all measures (p < 0.001). Only 30% of current cannabis users, believe cannabis should be legal to use in more public places, and only half of current users felt that Prop 64 made cannabis products and cannabis acquisition safer. Conclusions Four years after implementation, knowledge gaps around Prop 64 are widespread. Effective messaging is needed to increase awareness and bridge knowledge gaps, which can ultimately minimize public harm.